2016
DOI: 10.1161/circulationaha.115.018547
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Angiographic Findings in Acute Ischemic Stroke Patients With Elevated Cardiac Troponin

Abstract: Background-A relevant proportion of patients with acute ischemic stroke (AIS) have elevated levels of cardiac troponins (cTn). However, the frequency of coronary ischemia as the cause of elevated cTn is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 45 publications
6
82
0
7
Order By: Relevance
“…In contrast, readmission rates for ACS during the follow-up of patients diagnosed with type 2 MI and NIMI are lower than those for patients with type 1 MI, which suggests that a high proportion of these patients do not present with significant coronary lesions,27 28 a finding that should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, readmission rates for ACS during the follow-up of patients diagnosed with type 2 MI and NIMI are lower than those for patients with type 1 MI, which suggests that a high proportion of these patients do not present with significant coronary lesions,27 28 a finding that should be investigated in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…The recent TRELAS study found 24% of 29 AIS patients with hypertroponinemia had culprit lesions on coronary angiography, and 21% underwent mechanical revascularization. 30 . The number of culprit lesions was significantly lower than matched controls with AMI.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a massive catecholamine exposure may also lead to ischemic myocardial injury via coronary vasoconstriction or tachyarrhythmia especially in those with preexisting coronary artery disease (type 2 MI). The frequency of concomitant type 1 MI is unclear, but compared with age-and sex-matched patients with non ST-segment elevation ACS, patients with ischemic stroke were less likely to have coronary culprit lesions (7 of 29 vs 23 of 29; P Ͻ0.001) despite similarly increased cardiac troponin concentrations (46 ). Half of all stroke patients had no angiographic evidence of coronary artery disease at all in that study.…”
Section: Strokementioning
confidence: 85%